Estimasi Produktivitas Lahan Teh Menggunakan Metode NDVI Di Kabupaten Bandung - Siahaan, Yongky Samuel; Mataburu, Ilham Badaruddin; Sucahyanto, Sucahyanto (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the estimated productivity of tea land in Bandung Regency based on the results of Landsat 9 image analysis. This study used the Normalized Difference Vegetation Index method. NDVI values derived from Landsat 9 images were processed using the NDVI formula and then the NDVI values were analyzed using simple linear regression analysis with productivity variables to determine the equation for estimating tea land productivity. Data collection techniques in this study used primary and secondary techniques. The unit of analysis in this study is the community tea plantation area spread across 4 sub-districts, namely Ciwidey, Rancabali, Pasirjambu, and Pangalengan Districts. The result of this study is the estimation of tea land productivity based on the similarity of NDVI values with productivity data in the field. Based on the results of the study, NDVI value has an influence of around 57.6% on tea productivity. For the estimation of tea land productivity in 4 sub-districts, it was obtained at 2,312 tons / ha in 1 harvest which has a difference of 0.6 tons / ha from related agency data, namely at 1,996 tons / ha.